Pengaruh Intervensi Program Pencegahan HIV dan Aids Terhadap Pengetahuan dan Sikap Buruh di Proyek Pembangunan Fakultas Tehnik Unhas Gowa - Badwi, Adam; Gafur, Abdul; Munadhir, Munadhir (Jurnal Ushuluddin: Media Dialog Pemikiran Islam, 2017)
AIDS is a bunch of deseases sympton to those who are affected by virus (HIV). Up to now, the researchers have not yet found the medical solusion to tackle the virus. In relation to that, there are a number of strategies which are immediately required like acceleration program. The main objective of this research is to understand the influence of HIV intensive programs regarding the knowledge dan the attitude of labor workers. This research employs quantitative approach through pre-test and post test design. The authors come to conclude that there are any intervention influences after using peer education, and showing movies. There are many changes among the labor workers in terms of their knowledge. Their started to realize the huge impact of spreading virus HIV. However, according the research, showing movies to the object of research is more powerful than the others. It is hoped that the sustainability programs can increase the knowledge regarding HIV and AIDS.